Effect of Adding Poultrygrow 250 and Cr-Yeast in the Productive Performance and Some Health Aspects of Broiler Chicks: Galib. A. AL-Kassi , Faris A. Al-Obaidi , Shahrazad A. Al-Shadeedi and Raghad A. Abd Al-Jaleel - AL-Kassi, Galib. A. (The Iraqi Journal of Veterinary Medicine, 2006)
A total of 300 one day old unsexed broiler chicks were divided into threedietary groups which were: -T1: Un-treated control.T2: Poultrygrow 250 treated group.T3: Cr-Yeast treated group.Results have shown that the addition of Poultrygrow 250 and Cr-Yeasthave significantly (p < 0.05) improved the performance of broilers express inweight gain and feed conversion ratio compared with control group. The studyshowed an increase in red blood cell and hemoglobin and reduce in hetrophil /Lymphocyte ratio.It was concluded that the supplementation of poultrygrow 250and Cr-Yeast in the diet of broiler chickens could improve the performance ofthe birds.